ANALISIS KELAYAKAN USAHATANI BAYAM DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA KOTA PONTIANAK - Ardianto, Ardianto; Suyatno, Adi; Suharyani, Anita (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
This research aims to determine the Feasibility of Spinach Farming in Siantan Hilir Village, North Pontianak District. The research data used are primary and secondary data and a total of 39 farmers from a total sample population of 296 individuals using the slovin formula. The survey technique used was a survey technique for collecting samples through a random sampling method (simple random technique), technical sampling through interviews using a questionnaire tool.Â The research results provide evidence that the average income for spinach farming with a land size of less than 0.5 hectares is Rp. 8.25.431/MT and land size of more than 0.5 Ha as much as Rp. 688,688,-/MT, the R/C ratio of spinach farming with a land size of less than 0.5 Ha is also 1.75 and for land sizes above 0.5 Ha it is 1.14 while for price BEP and Production BEP with area land below 0.5 Ha, which is as much as Rp. 2,871 and 219.91 Kg while for land sizes above 0.5 Ha the price BEP and production BEP are Rp. 4,357.- and 862.6 Kg. This shows that spinach farming on a land area of less than 0.5 Ha is more feasible to cultivate when compared to spinach farming on a land area of more than 0.5 Ha.